2018
DOI: 10.1530/rep-17-0466
|View full text |Cite
|
Sign up to set email alerts
|

Early sex-dependent differences in response to environmental stress

Abstract: Developmental plasticity enables the appearance of long-term effects in offspring caused by exposure to environmental stressors during embryonic and foetal life. These long-term effects can be traced to pre-and post-implantation development, and in both cases, the effects are usually sex specific. During preimplantation development, male and female embryos exhibit an extensive transcriptional dimorphism mainly driven by incomplete X chromosome inactivation. These early developmental stages are crucial for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 135 publications
(119 reference statements)
1
37
0
1
Order By: Relevance
“…In developmental programming, early life exposure to maternal perturbations can lead to an increased risk of deleterious developmental consequences, and males are at a relatively greater risk of negative effects than females (Perez‐Cerezales et al . ). This greater susceptibility of males to deleterious in utero effects may account for the decreased number of male offspring.…”
Section: Discussionmentioning
confidence: 97%
“…In developmental programming, early life exposure to maternal perturbations can lead to an increased risk of deleterious developmental consequences, and males are at a relatively greater risk of negative effects than females (Perez‐Cerezales et al . ). This greater susceptibility of males to deleterious in utero effects may account for the decreased number of male offspring.…”
Section: Discussionmentioning
confidence: 97%
“…29 Early sex-dependent differences in response to environmental stress caused by sex chromosomes or hormones was suggested by several human and animal studies. 30 Nutrition could affect male infants more dramatically than female infants. 28 Hack et al also reported female VLBW infants had greater catch-up growth than male infants by 20 years old.…”
Section: Discussionmentioning
confidence: 99%
“…[72] In fact, many diseases with early developmental origins display sex biases. [73,74] Studies in rodent, bovine, and human blastocysts have shown that the response to environmental conditions is different in male and female embryos, [75,76] reflecting differences in their metabolism. [41,72] Also, there are evocative reports of sex-specific signaling by the embryo to the mother.…”
Section: Embryos Exhibit Sex-specific Responses To the Maternal Envirmentioning
confidence: 99%